Exploring the association between adolescent‐perceived parental monitoring on dietary intake - Bridie Osman; Katrina E. Champion; Louise Thornton; Tracy Burrows; Scarlett Smout; Emily Hunter; Matthew Sunderland; Maree Teesson; Nicola C. Newton; Lauren A. Gardner (Wiley, 2024)
Abstract Parenting practices such as parental monitoring are known to positively impact dietary behaviours in offspring. However, links between adolescent‐perceived parental monitoring and dietary outcomes have rarely been examined and never in an Australian context. This study investigated whether adolescent‐perceived parental monitoring is associated with more fruit and vegetable, and less sugar‐sweetened beverages (SSB) and junk food consumption in Australian adolescents. Cross‐sectional data was collected as part of baseline measurement for a randomised controlled trial in 71 Australian schools in 2019. Self‐reported fruit, vegetable, SSB and junk food intake, perceived parental monitoring and sociodemographic factors were assessed. Each dietary variable was converted to "not at risk/at risk" based on dietary guidelines, binary logistic regressions examined associations between dietary intake variables and perceived parental monitoring while controlling for gender and socio‐economic status. The study was registered in ANZCTR clinical trials. The sample comprised 6053 adolescents (Mage = 12.7, SD = 0.5; 50.6% male‐identifying). The mean parental monitoring score was 20.1/24 (SD = 4.76) for males and 21.9/24 (SD = 3.37) for females. Compared to adolescents who perceived lower levels of parental monitoring, adolescents reporting higher parental monitoring had higher odds of insufficient fruit (OR = 1.03; 95% CI = 1.02-1.05) and excessive SSB (OR = 1.07; 95% CI = 1.06-1.09) intake, but lower odds of excessive junk food (OR = 0.96; 95% CI = 0.95-0.98) and insufficient vegetable (OR = 0.97, 95% CI = 0.96-0.99) intake. Adolescent dietary intake is associated with higher perceived parental monitoring; however, these associations for fruit and SSB differ to junk food and vegetable intake. This study may have implications for prevention interventions for parents, identifying how this modifiable parenting factor is related to adolescent diet has highlighted how complex the psychological and environmental factors contributing to dietary intake are.